Storia e storia del diritto nell’Italia bassomedievale. Una discussione su O. Cavallar e J. Kirshner, Jurists and Jurisprudence in Medieval Italy. Texts and Contexts, 2020 - Guglielmotti, Paola; Varanini, Gian Maria (Reti Medievali Rivista, 2021)
Discussione del libro di O. Cavallar e J. Kirshner, Jurists and Jurisprudence in Medieval Italy. Texts and Contexts, 2020